KREATIVITAS KOMUNIKASI PEMASARAN MENCIPTAKAN TREN BARU DALAM BISNIS PHOTOBOOTH - Keysha Nadhiva Putri; Ira Hasianna Rambe, Mayumi Hanif Alzahra, Ardelia Rizki Andriyani, Navira Fathira Nurrahman, Rahma H (ADISAM PUBLISHER, 2026)
Increasingly intense competition within the photobooth industry compels business actors to adopt innovative and flexible marketing communication strategies. This study focuses on analyzing the creativity of marketing communication roles in shaping new trends within the KALT photobooth business, based on the AIDA (Attention, Interest, Desire, Action) model framework. This research employs a qualitative approach, with data collection methods including in-depth interviews with KALT photobooth staff and consumers, field observations, and literature reviews. The field observations aimed to directly examine the implementation of marketing communication strategies at the business locations. Supporting data were obtained from scientific publications and related literature to strengthen the analysis of the research findings. The findings of this study indicate that during the attention phase, customer interest is cultivated through visual concepts, themes, various photobooth configurations, and the introduction of innovative photo print formats such as flipbooks, primarily through social media platforms like TikTok and Instagram. The interest phase is manifested through distinctive visual elements that trigger customer curiosity regarding the service concept. In the desire phase, customer preference is influenced by short-form video content on TikTok that demonstrates the photobooth experience, as well as direct service from on-site promotional staff. The action phase is implemented through the customer's decision to utilize the photobooth service and engage in passive promotion, influenced by the synergy between social media and direct promotion. This research concludes that the implementation of the AIDA model effectively explains the function of creative marketing communication in establishing current trends within the photobooth business sector.